2015
DOI: 10.7819/rbgn.v17i58.2687
|View full text |Cite
|
Sign up to set email alerts
|

Non-financial reports, anti-corruption performance and corporate reputation

Abstract: Objective -This paper analyzes whether the anti-corruption reporting practices of the companies are a reflection of adequate anti-corruption systems put in place by companies, or whether the disclosure is merely a tool for companies to improve their reputation and thus maintain their legitimacy.Design/methodology/approach -We apply the PLS method to the collected data in a content analysis of the sustainability reports of 31 companies within the Ibex 35 in December 2008.Theoretical foundation -In the analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 62 publications
(107 reference statements)
2
20
0
Order By: Relevance
“…Only after this responsibility is met should organizations address the other interests of their stakeholders [6,8,10,11]. It appears that the composite indicator was very close to what the literature has been presenting as an economic and financial category [15,93,131]. This demonstrates that the stakeholders' perspectives are already recognized by the literature in this regard.…”
Section: Composite Indicators Extractionmentioning
confidence: 58%
See 2 more Smart Citations
“…Only after this responsibility is met should organizations address the other interests of their stakeholders [6,8,10,11]. It appears that the composite indicator was very close to what the literature has been presenting as an economic and financial category [15,93,131]. This demonstrates that the stakeholders' perspectives are already recognized by the literature in this regard.…”
Section: Composite Indicators Extractionmentioning
confidence: 58%
“…Their importance does not allow them to be ignored in this research. Thus, the first stage was configured by the construction of a list containing 95 social responsibility indicators, from the literature review of several theoretical and empirical articles on the topic [58][59][60]62,63,65,74,[76][77][78][79][80]82,[85][86][87][88][89][90]92,93,95,96,98,101,115]. The indicators were selected considering they should be related to the identified social responsibility dimensions; present in the largest number of reviewed literatures; or considered important and or complementary for the disclosure of PHEOs.…”
Section: Methodological Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies confirm that economic entities publish social and environmental information only to be within the limits of legality in the field in which they operate. It has also been found that less performing entities publish performance-related information [3].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…We can say that the companies in the technology industry would be most able to implement social responsibility programs, having the advantage of the latest technological discoveries, which facilitate their activity, these corporations being suitable to conclude collaborations/coalitions in order to design a better future. Large IT companies say they are investing considerable amounts in order to discover renewable energy sources, they are investing in the education sector and they are supporting young people in finding a job, they are taking measures to reduce water consumption and carbon emissions, they are investing in the medical sector, advocates for well-being and safety at work [3]. The technological sector can also be used effectively to influence the public's decision, in order to act in favor of developing the social environment.…”
Section: Cosmetic Industrymentioning
confidence: 99%